Death and Life: A Study on Pakistani Youth - Rattani, Sarwat Amin; Iqbal, Dr. Farah (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
The aim of the present study was to explore the relation between Death Attitudes and Meaning in Life. Besides this exploratory approach, it was also hypothesized that Search for Meaning would be significantly greater than Presence of Meaning in youth population. For this purpose, 60 males and 60 female students were conveniently approached in University of Karachi to participate in the study. Two questionnaires were administered; Death Attitudes Profile Revised (subscales; fear of death, death avoidance, neutral acceptance, approach acceptance and escape acceptance) and Meaning in Life (subscales; search for meaning and presence of meaning). Results revealed gender difference in two death attitudes. Hypothesis regarding search for meaning being greater than presence of meaning was proved. Exploratory analysis of death attitudes and meaning in life showed complex relation.The aim of the present study was to explore the relation between Death Attitudes and Meaning in Life. Besides this exploratory approach, it was also hypothesized that Search for Meaning would be significantly greater than Presence of Meaning in youth population. For this purpose, 60 males and 60 female students were conveniently approached in University of Karachi to participate in the study. Two questionnaires were administered; Death Attitudes Profile Revised (subscales; fear of death, death avoidance, neutral acceptance, approach acceptance and escape acceptance) and Meaning in Life (subscales; search for meaning and presence of meaning). Results revealed gender difference in two death attitudes. Hypothesis regarding search for meaning being greater than presence of meaning was proved. Exploratory analysis of death attitudes and meaning in life showed complex relation.